Environmental Consciousness and Moral Hazard in International Agreements to Protect the Environment / Centre of Planning and Economic Research: No 34. - Petrakis E; Xepapadeas A (,́, 1994)
Introduction, First-Best Optimum and Stable Coalitions, Enforcing the Agreement under Moral Hazard, Summary, References.